2021
DOI: 10.1016/j.amsu.2021.102213
|View full text |Cite
|
Sign up to set email alerts
|

Columella reconstruction using double nasolabial flap and costal cartilage: A case report

Abstract: Total loss of columella causes significant aesthetic and functional deformities due to its important functions which provides assistance and extension to the nose pointer. Noma is described as one of the developed sources of total columellar loss, and is also contagious, with the ability to intensely damage facial tissues and immediate structures. However, the condition is predominantly suffered in Africa, with an estimation of 20 instances per 100,000 individuals. Furthermore, the reformation of a columellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…There are no conflicts of interest or funding supports to declare. Julia Montero-Menárguez MD 1 Víctor Onecha-Vallejo MD…”
Section: Ackno Wle Dge Mentsmentioning
confidence: 99%
“…There are no conflicts of interest or funding supports to declare. Julia Montero-Menárguez MD 1 Víctor Onecha-Vallejo MD…”
Section: Ackno Wle Dge Mentsmentioning
confidence: 99%
“…The most commonly used classification systems for noma surgical programs are the Montandon system which focuses classification on the area of the face implicated [48], the WHO noma classification system which classifies noma according to distinct stages of clinical progression [3] and the nose, outer lining, inner lining, trismus, upper lip, lower lip, particularities (NOITULP) grading tool which classifies noma cases based on the percentage loss of each anatomical unit [49]. Appropriate reconstructive surgery is performed to repair defects and restore esthetic form and function, utilizing local, regional, pedicled, and free flaps along with surgery of the craniofacial skeleton [23,24,28,29,33,48,[50][51][52][53]. Surgical plans are formulated from a multidisciplinary group, with special consideration for airway management, postoperative care settings, and physical therapy needs.…”
Section: Care For Patients With Sequelaementioning
confidence: 99%
“…The focus of recent literature on noma (2019–2021) includes noma's distribution and risk factors [17–19], treatment [20–34], knowledge and beliefs about the disease [14,35–37] along with reviews of the literature and viewpoints [38–41]. Recent literature (2019–2021) has shown that noma cases are being reported from an increasingly diverse set of geographical locations outside of Africa including China [22,28], India [23], Vietnam, [24] and Indonesia [33] (Fig. 3).…”
Section: Neglect Of Noma Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Many methods have been used for nasal reconstruction, for instance, dermal regeneration (intergra), skin grafts, and different kinds of skin flaps (frontal flap, frontonasal flap, nasolabial flap) 1 . The nasolabial flap is one of the most commonly used methods for facial reconstruction surgeries 2 , with almost 100% survivability 3 . However, standard nasolabial flaps have some drawbacks, including a lack of proper curvature and difficulties to aesthetically blend with surrounding structures, especially in alar rim reconstructive surgeries 4 .…”
Section: Introductionmentioning
confidence: 99%